Sister's choice - Richards, Emilie, 1948- (Don Mills, Ont. : Mira, 2008)
Childless Kendra and husband Isaac accept an offer from Kendra's younger sister- single mom Jamie- to conceive and carry a child for them. But when a medical crisis threatens Jamie's health she learns that the most difficult choice in her life is yet to come
Keywords: Sisters -- Fiction; Surrogate mothers -- Fiction; Surrogate motherhood -- Fiction; Shenandoah River Valley (Va. and W. Va.) -- Fiction; Domestic fiction